Evaluation of the gold nanoparticles prepared by ‎green ‎chemistry in ‎the ‎‏treatment of cutaneous candidiasis - Hassan Kareem; Hayder Samaka; Wasna'a Abdulridha (Mazandaran University of Medical Sciences, 2021)
Background and Objectives: Mineral nanoparticle synthesis via green chemistry is ‎considered a novel ‏procedure ‎that ‎has been introduced into some ‏‎‎industries and medical fields. This ‎paper aimed to focus on ‏synthesized gold ‎nanoparticles ‎‎‎‎(‎AuNPs‎) prepared via green chemistry and ‎their usage in the ‏treatment of cutaneous ‎candidiasis.‎‎ Materials and Methods: This study was performed on the green synthesis of AuNPs using olive leaf extract as a reducing ‎agent‎. The ‎UV‎ visible spectroscopy, X-ray diffraction, and atomic force microscopy techniques ‎were used to detect ‏the concentration of the prepared AuNPs‎. ‎The agar gel diffusion method was used to test ‏the ‎antifungal activity of the ‎‎prepared AuNPs in vitro. ‏Antifungal efficacy of the AuNPs in vivo ‎was tested by the ‎induction of‎‎ cutaneous ‎candidiasis in mice‎. ‎This research was conducted on four groups of mice‎. Groups 1 and 2 were used to evaluate the effectiveness of the AuNPs suspension ‎and ‏Nystatin ointment in the treatment ‎of clinical infection, respectively. Groups 3 ‎and ‎4 were the infected ‎and the non-infected control groups, respectively.‎ Results: Based on the findings, the AuNP synthesis using olive leaves was ‎a suitable and ‎secure method. Moreover, it was found that the AuNP concentration of 40.77 ng‏\‏ml represented the minimum ‎inhibitory concentration for the ‎inhibition of the Candida albicans. The prepared AuNPs were more effective than Nystatin ‎in the ‏treatment ‎of cutaneous candidiasis.‎‎ Conclusion: Preparation of AuNPs via green chemistry using olive leaves as a reducing ‎agent is a ‏safe ‎and easy procedure that can be performed to produce AuNPs. In this study, the AuNPs ‎displayed antifungal ‏activity ‏both in vitro and in vivo.